2022
DOI: 10.1038/s41417-022-00431-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the stability and intratumoral delivery of foreign transgenes encoded by an oncolytic Foamy Virus vector

Abstract: Foamy Viruses are cell cycle-dependent retroviruses capable of persisting unintegrated in quiescent cells until cell division occurs. This unique ability allows them to target slowly dividing human tumor cells which remains an unmet need in oncolytic virotherapy. We have previously reported the generation of oncolytic Foamy Virus (oFV) vector system and demonstrated its superiority over oncolytic Murine Leukemia Virus vectors in infecting slowly dividing cancer cells. In the present study we evaluated (i) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…These vectors can successfully infect multiple human cancer cells with slow kinetics, which resulted in growth arrest and prolonged survival in animal models [ 243 , 244 ]. In 2022, Budzik generated foamy viral oncolytic vectors carrying thymidine kinase and inducible caspase 9 [ 245 ]. These vectors are able to stably carry and express transgenes upon serial passage, suggesting foamy viruses as a promising oncolytic virus for OVT [ 245 ].…”
Section: Medical Applications Of Retroviral Integration Site Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These vectors can successfully infect multiple human cancer cells with slow kinetics, which resulted in growth arrest and prolonged survival in animal models [ 243 , 244 ]. In 2022, Budzik generated foamy viral oncolytic vectors carrying thymidine kinase and inducible caspase 9 [ 245 ]. These vectors are able to stably carry and express transgenes upon serial passage, suggesting foamy viruses as a promising oncolytic virus for OVT [ 245 ].…”
Section: Medical Applications Of Retroviral Integration Site Selectionmentioning
confidence: 99%
“…In 2022, Budzik generated foamy viral oncolytic vectors carrying thymidine kinase and inducible caspase 9 [ 245 ]. These vectors are able to stably carry and express transgenes upon serial passage, suggesting foamy viruses as a promising oncolytic virus for OVT [ 245 ]. Nonetheless, a better understanding of the strategies developed by retroviruses to ensure efficient integration and replication will be of great interest in order to engineer and optimize future OVT applications.…”
Section: Medical Applications Of Retroviral Integration Site Selectionmentioning
confidence: 99%
“…A strategy to use producer cells as a buffer between a therapeutic virus as well as the patient's immune system was developed as a result of this finding. 29 Multiple laboratories' studies showed that various stem cell lineages could act as vehicles for the undetected in vivo distribution of an F I G U R E 1 An illustration of the overview of oncolytic virotherapy for the treatment of glioblastoma multiforme. Therapeutic characteristics of oncolytic virotherapy and methods for its enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…The early in vivo studies with OVs showed that anticancer effect may not be brought on by the virus itself, but rather by the infected virus‐producing cells. A strategy to use producer cells as a buffer between a therapeutic virus as well as the patient's immune system was developed as a result of this finding 29 . Multiple laboratories' studies showed that various stem cell lineages could act as vehicles for the undetected in vivo distribution of an oncolytic adenovirus to treat glioblastoma 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, zoonotic infections with gorilla SFV were found to be associated with hematological abnormalities and altered biochemical markers [ 9 ]. In addition, foamy viruses represent potential vector platforms for gene therapy [ 14 , 15 , 16 , 17 ] or oncolytic therapy [ 18 , 19 ], which warrants study of their cell entry mechanisms.…”
Section: Introductionmentioning
confidence: 99%